2010
DOI: 10.1016/j.jplph.2010.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and accumulation of manganese and cadmium in the manganese accumulator Lupinus albus

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 32 publications
(23 reference statements)
2
22
0
Order By: Relevance
“…The presence of these compounds is one of the symptoms of Mn toxicity in plants (Zornoza et al, 2010). In addition to this symptom, other symptoms related to situations of Mn toxicity, such as browncolored lesions (Wissemeier & Horst, 1992), loss of apical dominance, shriveling of leaves (El-Jaoual & Cox, 1998;Marschner, 2012) and splitting of lateral shoots, are also frequently found in plants with ESBVRD.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of these compounds is one of the symptoms of Mn toxicity in plants (Zornoza et al, 2010). In addition to this symptom, other symptoms related to situations of Mn toxicity, such as browncolored lesions (Wissemeier & Horst, 1992), loss of apical dominance, shriveling of leaves (El-Jaoual & Cox, 1998;Marschner, 2012) and splitting of lateral shoots, are also frequently found in plants with ESBVRD.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of some of the important plant macro, micro and beneficial elements in alleviating Cd toxicity in plants is summarized below. Triticum aesitivum Increases ATP-S activity [5] Brassica juncea Increases GSH content [6,68] Ca Arabidopsis thaliana Decreases Cd content [77] Trifolium repens Decreases Cd accumulation [78] Mg Oryza sativa L. Decreases genes expression for Cd transport [80] Lupinus albus Protects photosynthetic tissues [86] Zn Triticum durum Addition of Zn to soil reduced crop Cd concentrations [95] Oryza sativa Inhibits Cd uptake [30] Brassica chinensis Suppresses Cd uptake and root-to-shoot transport [90] Arachis hypogaea Reduces shoot Cd accumulation and a stimulation of antioxidative enzymes [10] Se…”
Section: Plant Mineral Nutrients In Alleviation Of Cadmium Toxicitymentioning
confidence: 99%
“…The Mn-mediated amelioration of Cd-induced root growth inhibition in maize seedlings has been shown to be associated with parallel reductions in Cd uptake [85]. In a study on lupine, Zornoza et al [86] found that supplementation of MnSO 4 to Cd-treated plants played a protective role in photosynthetic tissues against Cd stress and increased the antioxidant capacity of root together with high leaf Mn concentration. The effects of Mn starvation reducing Cd uptake and plant concentration indicated that this Mn-Cd interaction was not due to true cation antagonism, but they share a common transport site or process [42].…”
Section: Micro Nutrientsmentioning
confidence: 99%
“…Manganese is an indispensable trace element constituting the reactive centers of various enzymes and is more than 20 times the amounts of the other metal pollutants in the V-Ti tailings. It should be noted that excessive ingestion of Mn can also cause toxicity to both plants and bacteria (Zornoza et al, 2010). Investigations by predecessors discovered that although Mn exists in plants in fairly large amounts, its toxicity can still affect the bacterial growth and legume-rhizobia associations (de Varennes et al, 2001; Hayes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%